(3aQGFO GdbdGFO aj eNJUQ TQM GdahGFOs - (3GdYjfj, CHh eMeO, HOQ GdOjf, eMehO Hf CMeO Hf ehSi, J (B855(3g` (B1451(3es ((3efjQ Ydj Hf MSjf Ydjs)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg MeOG JbOjQg MeOJ Gddg MeOG hCMeO Gddg MeOG ajchf GfJUGH MeOG Ydi Cfg eaYhd daYd ebOQ hPdc ceG aj bhdg UHZI Gddg hGdJbOjQ UHZ Gddg UHZIs
(3BNQgG (B:s
(3BNQgG(B: (3GdYdj GdLd GdhGSY GdhGgH GdaVd GdhghH GdeLRd(B. (3bGdg CHh GdfLe GdYLdj GdTGgO aj GdBLGd MjK de jOZe eY GdehLH ddVQhQI hGdhghH eHGdZI hGgH hGdeLRd ef CLRd Cj CYWi YWGA cKjQG (B. (3hgPG BNQ eG GNJUQfGg ef GdThGgOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 163s
(3cTa GdXfhf, L (B2: 1066s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs